2021
DOI: 10.3390/tropicalmed6040189
|View full text |Cite
|
Sign up to set email alerts
|

Of Mice, Cattle, and Men: A Review of the Eco-Epidemiology of Leptospira borgpetersenii Serovar Ballum

Abstract: In New Zealand (NZ), leptospirosis is a mostly occupational zoonosis, with >66% of the recently notified cases being farm or abattoir workers. Livestock species independently maintain Leptospira borgpetersenii serovar Hardjo and L. interrogans serovar Pomona, and both are included in livestock vaccines. The increasing importance in human cases of Ballum, a serovar associated with wildlife, suggests that wildlife may be an overlooked source of infection. Livestock could also act as bridge hosts for humans. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 117 publications
(156 reference statements)
1
11
0
Order By: Relevance
“…Ballum is not in any of the available bacterins, and it is not commonly included in many MAT panels. The data here as well as in previous studies show it is a serogroup of concern [ 38 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Ballum is not in any of the available bacterins, and it is not commonly included in many MAT panels. The data here as well as in previous studies show it is a serogroup of concern [ 38 ].…”
Section: Discussionsupporting
confidence: 88%
“…A seroprevalence study showed that cattle have been exposed to serogroup Ballum in the U.S. [ 12 ]. Ballum is emerging as an important problem in humans and animals in New Zealand [ 38 ]. The L. borgpetersenii serogroup Ballum has been isolated from rodents, and it is virulent in the hamster model, which emulates the pathology associated with acute lethal forms of human leptospirosis [ 28 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the 1950s -1970s investigated NZ wildlife as a potential reservoir of Leptospira [18]. Black rats (Rattus rattus), brown rats (R. norvegicus), house mice (Mus musculus) and hedgehogs (Erinaceus europaeus) were described as maintenance hosts for Ballum and possums (Trichosurus vulpecula) for Balcanica [19].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to numerous countries worldwide, rodents and wildlife at the time were identified as a minor public health concern for leptospirosis in NZ [20][21][22]. At the time, Ballum was rarely reported (< 1%) in the notified human cases and thus did not warrant investment into research on Leptospira infection in wildlife [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation